Evaluating Psychometric Properties of Raven’s Coloured Progressive Matrices Test in Indonesian Sample using the Rasch Model - Yonathan Natanael; Irfan Fahmi; Dini Utami Mulyaningsih (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Coloured Progressive Matrices (CPM) is a psychological test well known among Indonesian psychologists to measure intelligence. Some researchers who use CPM in their research reveal that CPM has weaknesses in the principle of measurement equivalence. Therefore, the focus of this research is to evaluate the details of the psychometric properties of CPM by using the Rasch model. This research used a secondary data analysis approach, where the primary data sets from a psychological service were collected into a single file for further analysis. Data of 371 boys and 377 girls with an age range of five to seven years old who took an intelligence test to assess their school readiness were collected. The Rasch model analysis showed that CPM showed unidimensionality and local independence, had a fairly good reliability value, and eight items were unsuitable for testing intelligence. Only twenty-eight items of CPM were suitable for measuring children’s intelligence in Indonesia